The Role of Digital Literacy in Mediating Product Creativity and The Competitiveness of Housewives Market Snacks in Makassar - Rifah Shafwah; Masradin Masradin; Afiah Mukhtar; Alfina Damayanti (Poltanesa, 2026)
Market snack businesses, which are generally managed by housewives, face problems to maintain competitiveness because they are in a digital market environment. Product creativity, although important for differentiation, is not strong enough to increase competitiveness without the support of digital literacy. This study aims to analyze the mediating role of digital literacy in the relationship between product creativity and competitiveness. This research was conducted in Indonesia, specifically in Makassar City. Research with 135 respondents using a quantitative approach, hypothesis testing was carried out using SEM-PLS. The results show that product creativity has a significant effect on digital literacy and competitiveness, although the direct influence on competitiveness is relatively weaker than the mediated path. Digital literacy has a positive and significant effect on competitiveness and plays an important role as a mediator of the relationship between product creativity and competitiveness. These findings suggest that creativity in product variety, packaging, and innovation is the basis for business differentiation, but sustainable competitiveness is more effectively achieved when combined with digital literacy. Theoretically, this study emphasizes digital literacy as a strategic capability of MSMEs, while practically emphasizing the importance of improving digital skills for market snack business actors to optimize creativity and expand market opportunities. Therefore, enhancing digital literacy among housewives is crucial for sustaining their market snack businesses in the competitive digital economy.